Water resources: Need for a holistic approach - Reddy, A. Ranga (2003)
Construction of large dams has been the mainstay of government's water resource development policy. In the process traditional means of water storage and management like lake, tanks and wells have been largely ignored. The prevailing situation of groundwater depletion, silting of water bodies and water pollution can be attributed to unscientific utilisation of the resources. While discussing these aspects, the article touches upon issues like sustainability, inter-basin linking and privatisation of drinking as well as irrigation water supply. A specific study has been made on the water scarcity situation of Tamil Nadu. The authors put forward a number of suggestions on the basis of the success of Tamil Nadu experiment. - Reproduced.
Keywords: Water resources management